Gonadoblastoma in Turner syndrome and Y-chromosome-derived material - Mazzanti, Laura; Cicognani, Alessandro; Baldazzi, Lilia; Bergamaschi, Rosalba; Scarano, Emanuela; Strocchi, Simona; Nicoletti, Annalisa; Mencarelli, Francesca; Pittalis, Mariacarla; Forabosco, Antonino; Cacciari, Emanuele (American journal of medical genetics. Part A, 2005)
The identification of Y‐chromosome material is important in females with Ullrich–Turner syndrome (UTS) due to the risk of developing gonadoblastoma or other gonadal tumors. There is controversy regarding the frequency of the Y‐chromosome‐derived material and the occurrence of gonadoblastoma in these patients. The aim of our study was to evaluate a large number of patients with UTS, followed before and during the pubertal age for the prevalence of Y‐chromosome derived material, the occurrence of gonadoblastoma, and the incidence of possible neoplastic degeneration. An unselected series of 171 patients with UTS (1–34 years old), diagnosed cytogenetically, was studied for Y‐chromosome markers (SRY and Y‐centromeric DYZ3 repeats). The follow‐up was of 2–22 years; 101 of these patients were followed during pubertal age. Y‐chromosome material was found in 14 patients (8%): 12 of these were gonadectomized (2.8–25.9 years). A gonadoblastoma was detected in four patients under 16 years of age: in two, Y‐material was detected only at molecular analysis (at conventional cytogenetic analysis, one was included in the 45,X group and one in the X + mar group) and one had also an immature teratoma and an endodermal sinus carcinoma. The prevalence of gonadoblastoma in our series of gonadectomized UTS patients with Y‐positive material was of 33.3% (4/12). Our data suggest that the age of appearance and the possibility of malignant degeneration of gonadoblastoma can occur early in life. These patients, in particular those with 45,X or a marker chromosome may benefit from molecular screening to detect the presence of Y‐chromosome material; PCR is a rapid and inexpensive technique. At the moment, laparoscopy and preventive gonadectomy performed as soon as possible remain the procedures of choice for patients with UTS, when Y‐chromosome has been identified, as we are still unable to predict a future malignant evolution of gonadoblastoma. © 2005 Wiley‐Liss, Inc.